Operant Up-Conditioning of the Tibialis Anterior Motor-Evoked Potential in Multiple Sclerosis: Feasibility Case Studies - Aiko K. Thompson; Briana M. Favale; Jacqueline Velez; Patricia Falivena (Neural Plasticity)
Damage to the corticospinal pathway often results in weak dorsiflexion of the ankle, thereby limiting the mobility of people with multiple sclerosis (MS). Thus, strengthening corticospinal connectivity may improve locomotion. Here, we investigated the feasibility of tibialis anterior (TA) motor-evoked potential (MEP) operant conditioning and whether it can enhance corticospinal excitability and alleviate locomotor problems in people with chronic stable MS. The protocol consisted of 6 baseline and 24 up-conditioning sessions over 10 weeks. In all sessions, TA MEPs were elicited at 10% above active threshold while the sitting subject provided 30–35% maximum voluntary contraction (MVC) level of TA background EMG. During baseline sessions, MEPs were simply measured. During conditioning trials of the conditioning sessions, the subject was encouraged to increase MEP and was given immediate feedback indicating whether MEP size was above a criterion. In 3/4 subjects, TA MEP increased 32–75%, MVC increased 28–52%, locomotor EMG modulation improved in multiple leg muscles, and foot drop became less severe. In one of them, MEP and MVC increases were maintained throughout 3 years of extensive follow-up sessions. These initial results support a therapeutic possibility of MEP operant conditioning for improving locomotion in people with MS or other CNS disorders, such as spinal cord injury and stroke.